REKONSTRUKSI MANAJEMEN PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM BERBASIS KOMPETENSI ABAD 21 - Azriel Muhammad Faza Yusuf; Muhamad Ali Sidik (Universitas Islam Bunga Bangsa Cirebon, 2023)
This study aims to reconstruct the management of Islamic education curriculum development based on 21st century competencies, focusing on the gap between the existing curriculum framework and the actual demands of contemporary learning needs. The urgency of this research arises from the persistent misalignment between the normative-ideological foundations of Islamic education and the practical requirements of modern competency-based approaches, including critical thinking, communication, collaboration, and creativity. Employing a systematic literature review methodology, this study critically examined thirty-five peer-reviewed sources published between 2020 and 2025, integrating theoretical frameworks from curriculum management, Islamic educational philosophy, and competency-based education. The findings reveal that effective reconstruction requires a tripartite model encompassing: (1) epistemological reorientation of curriculum design toward tawhidic integration, (2) managerial restructuring of planning, implementation, and evaluation cycles, and (3) contextual adaptation of 21st century skill frameworks within Islamic value systems. This study contributes a conceptual model termed Integrated Competency-Based Islamic Curriculum Management (ICBICM) that bridges normative Islamic values with empirical competency demands, offering practical implications for madrasah administrators, Islamic school principals, and curriculum developers